Etnoekologi Masyarakat Samin Kudus Jawa Tengah - Jumari, Jumari; Setiadi, Dede; Purwanto, Y; Guhardja, Edi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2012)
The study of the ethnoecology of Samin Society in Kudus been conducted in March 2011 to August 2011. The aim of this study was to review and document local knowledge of of Samin Society about their views of the environment. The location is Larikrejo and Kaliyoso villages, Undaan District, Regency of Kudus. Data collection techniques with direct field observation, open interviews (open ended), structured interviews with key informants, and focus group discussions (FGD). Results of research on local resource management in communities samin illustrated on describtif phenomenology. Theirs traditional knowledge about the environment is reflected in the form of land use management systems. Environmental unit and production activities such as: rice fields, yards, dry field, swamps, embung and rivers. Samin community interaction with the environment is very strong, like wong (humans) with sandang pangan (food and clothing), or like living with a livelihood. Society's view of land interests change with the change of environmental conditions and their knowledge level.Â Key word: Ethoecology, local knowledge, Samin Society, view of invironment, environmental unit